Determination of the Activation Energy for Desorption by Derivative Thermogravimetric Analysis - Xiang Li; Hai-Fu Guo; Hua-Ming Chen (Adsorption Science & Technology)
A method using derivative thermogravimetric analysis (DTG) was proposed for estimating the activation energy for the desorption of low volatile compounds on activated carbon. For such purposes, a fast Fourier-transform (FFT) filter was adapted to improve the signal-to-noise ratio of the DTG response curve. A series of TG experiments were carried out to determine the respective TG spectra of dibenzofuran and 1-hexanol desorbed from NORIT RB1, NORIT PK and Chemviron BPL activated carbons, from which DTG curves were calculated. DTG spectra filtered using FFT allowed the corresponding activation energies for the desorption of dibenzofuran and 1-hexanol from the three activated carbons to be estimated. A relationship with the microporosity was found indicating that the narrower the mean pore diameter of an activated carbon, the higher was the activation energy for desorption.